Resilience of Parents who Have Children with Cancer - Fransiska Riati Sutanti Tumanggor; Nur Setiawati Dewi; Anggorowati (STRADA : Jurnal Ilmiah Kesehatan, 2023)
Cancer is one of the diseases that causes death in children in the world. The incidence of cancer globally every year is as many as 300 thousand children. Cancer that occurs in children causes major reactions in parents that are often associated with trauma and shock. Parents suffer from psychosocial problems, financial tensions, social isolation and conflicts of work and family roles and reduced time for other children and recreational activities. The main key in overcoming the problem of children with cancer is resilience. Research on the resilience of parents who have children with cancer is still limited. The absence of a literature study in the form of a scoping review of the resilience of parents who have children with cancer has made researchers interested in conducting literature studies. A systematic review is needed to disseminate the relevant literature on the resilience of parents who have children with cancer.